INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Dewi, Nisa Ayu Castrena; Isynuwardhana, Deannes (University of Merdeka Malang, 2014)
Company competition ability was not only in the assets ownership but also in the innovation, informationsystem, organization management and resources, including the importance of knowledge assets in the company.One of the approaches used in assessment and measuring of knowledge assets was Intellectual Capital(IC) which used model namely Value Added Intellectual Coefficient (VAICTM) and also used per IC componentnamely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and StructuralCapital Value Added (STVA). This research aimed to investigate the intellectual effect toward firm value withreturn on assets as the intervening variable. The samples of this research were pharmacy companies listed inBEI. The samples were selected by using purposive sampling method and there were 24 observation data. Thehypotheses of this research used path analysis, simple linear regression and double linear regression. Theresult of this research showed that IC had a positive significant effect toward Return on Assets as. IC did nothave a direct effect toward firm value. It influenced indirectly toward firm value with Return on Assets as theintervening variable, simultaneously or partially. VACA, VAHU and STVA did not have an effect towardReturn on Assets of a firm simultaneously or partially. VACA, VAHU and STVA did not have an effect onfirm value.